2017
DOI: 10.1021/acsomega.7b00973
|View full text |Cite
|
Sign up to set email alerts
|

Zero-Dimensional Methylammonium Bismuth Iodide-Based Lead-Free Perovskite Capacitor

Abstract: Symmetrical electrochemical capacitors are attracting immense attention because of their fast charging–discharging ability, high energy density, and low cost of production. The current research in this area is mainly focused on exploring novel low-cost electrode materials with higher energy and power densities. In the present work, we fabricated an electrochemical double-layer capacitor using methylammonium bismuth iodide (CH 3 NH 3 ) 3 Bi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 33 publications
1
61
0
Order By: Relevance
“…The possiblities of low‐dimensional perovskites have also been explored in some other applications, such as memory devices, batteries, and capacitors . Previously, we reported the first demonstration of applying 3D perovskite MAPbI 3− x Cl x in nonvolatile memory devices, indicating a remarkable appearance of resistive switching effect with a small on‐off voltage (<1 V) in a simple configurature of Au/perovskite/FTO (Figure a and b) .…”
Section: Applications Beyond Photovoltaicsmentioning
confidence: 98%
See 2 more Smart Citations
“…The possiblities of low‐dimensional perovskites have also been explored in some other applications, such as memory devices, batteries, and capacitors . Previously, we reported the first demonstration of applying 3D perovskite MAPbI 3− x Cl x in nonvolatile memory devices, indicating a remarkable appearance of resistive switching effect with a small on‐off voltage (<1 V) in a simple configurature of Au/perovskite/FTO (Figure a and b) .…”
Section: Applications Beyond Photovoltaicsmentioning
confidence: 98%
“…Based on computational and experimental studies, it was found that the lithium conversion mechanism is more energetically favorable than conventional lithium intercalation processes . Furthermore, the first attempt of 0D perovskite MA 3 Bi 2 I 9 in the electrochemical double‐layer capacitor was also investigated very recently, delivering a maximum areal capacitance of 5.5 mF cm −2 with 84.8% retaining after 10 000 charge‐discharge cycles (Figure g and h) …”
Section: Applications Beyond Photovoltaicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Johnpaul et al. fabricated an electrochemical double‐layer capacitor using methylammonium bismuth iodide (CH 3 NH 3 ) 3 Bi 2 I 9 material and reported areal capacitance of 5.5 mF cm −2 at scan rate of 5 mV s −1 …”
Section: Introductionmentioning
confidence: 99%
“…Johnpaul et al fabricated an electrochemical double-layer capacitor using methylammonium bismuth iodide (CH 3 NH 3 ) 3 Bi 2 I 9 material and reported areal capacitance of 5.5 mF cm À 2 at scan rate of 5 mV s À 1 . [28] We therefore report the design and fabrication of CdS quantum dots and organohalide perovskite-based bilayer electrodes for symmetric electrochemical capacitors. For comparative study, three different symmetric electrochemical capacitors were fabricated viz: CdS quantum dots (CSQDs) single layer electrodes, CdS quantum dots and methyl ammonium lead iodide (CSQDs-MPI) bilayer electrodes and CdS quantum dots and methyl ammonium bismuth iodide (CSQDs-MBI) bilayer electrodes.…”
Section: Introductionmentioning
confidence: 99%